HUBUNGAN KECANDUAN MEDIA SOSIAL DENGAN SELF-REGULATED LEARNING PADA MAHASISWA KEPERAWATAN UNIVERSITAS UDAYANA SELAMA PEMBELAJARAN JARAK JAUH DI MASA PANDEMI COVID-19 - Mutiara, Kadek Citra; Krisnawati, Komang Menik Sri; Rahajeng, Indah Mei (Coping: Community of Publishing in Nursing; Vol 12 No 3 (2024): Juni 2024, 2024)
Along with technological advances, social media has developed significantly as a multifunctional communication media. Interesting features and ease of use provide a pleasant effect so that it is used continuously by students and that it can cause addiction to social media. Social media addiction has an impact on self-regulated learning (SRL) so that it can affect academic results. This research aims to determine the relationship between social media addiction and SRL in nursing students of Udayana University during distance learning in the COVID-19 pandemic. The design of this research uses a descriptive correlation with cross sectional approach. The sample was nursing students of Udayana University who were selected using probability sampling with a proportional stratified random sampling technique (n=170). The independent variable of this study is social media addiction, while the dependent variable is SRL. Data were collected using a modified Social Media Addiction questionnaire by Sugianto (2017) which has been adapted from Internet Addiction Test by Young (1998) and Self-Regulated Learning questionnaire by Putri (2017) which was adapted from Wolters' (2003) SRL scale. The results of the analysis using the Spearman rank correlation obtained a p-value of  0.000<0.05, which means there is a significant relationship between social media addiction and SRL. So it can be concluded that there is a relationship between social media addiction and SRL in nursing students of  Udayana University during distance learning in the COVID-19 pandemic. Students are expected to control the use of social media and improve SRL to support a better academic process.